Integrasi Mobile Pocket Book dalam Pembelajaran Berbasis Masalah untuk Meningkatkan Kemampuan Pemecahan Masalah Fisika Peserta Didik - Rindayu Noviatika; Gunawan Gunawan; Joni Rokhmat (Indonesian Journal of Teacher Education, 2021)
This study aims to analyze the effectiveness of integrating a mobile pocket book into the Problem-Based Learning (PBL) model to enhance students' physics problem-solving skills. A quasi-experimental research with a non-equivalent control group design was conducted involving 11th-grade science students selected through cluster random sampling as experimental and control groups. Data were collected using a validated and reliable essay test measuring problem-solving skills and analyzed using N-gain and independent sample t-tests. Statistical results revealed that tcount > ttable (5.832 > 2.003), indicating a significant difference in effectiveness between the two groups. The N-gain score for the experimental class reached 60.3% (medium category), significantly higher than the control class at 33.8% (medium category). The 'understanding' indicator achieved the highest increase in both classes, while 'applying' reached a medium category in the experimental group and a low category in the control group. Conversely, 'selecting' and 'identifying' indicators showed relatively low increases across both groups. Integrating a mobile pocket book into PBL effectively optimizes students' physics problem-solving skills, particularly in understanding and applying concepts.